Forward to the Past? New/Old Theatres of Russia's International Projection - Eleonora Tafuro Ambrosetti (Pubblicazioni ISPI, 2020)
Russia seems to be back in many "old" theatres where the Soviet Union was actively engaged. More than a quarter of a century after the fall of the USSR, it is clear that Russia's President Vladimir Putin has made restoring Russia's great power status a primary goal of his twenty years in power. Political and historical links dating back to the Cold War have been capitalised upon to build fresh partnerships and cement or re-establish Russia's influence in Africa, Latin America and the Middle East. Just as the Soviet Union supported Western communist parties and ran disinformation campaigns, today's Russia is accused of meddling with the electoral processes of several Western countries. What are the elements of continuity and change when comparing Russia's foreign policy with the Soviet Union's? This ISPI Report tackles the political, historical, military and economic dimensions of Russia's return to old Soviet theatres of influence. In particular, it delves into their implications for the development of the multipolar world order long-advocated by Moscow.